Mixed matrix membrane based on ZIF-8 and MXene as well as preparation method and application of mixed matrix membrane

By introducing ZIF-8@MXene nanosheets into the polymer gas separation membrane, the problem of difficulty in taking into account both selectivity and permeability of the existing membrane is solved, and efficient gas separation performance is achieved, which is suitable for industrial applications.

CN119455696APending Publication Date: 2025-02-18JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411770469.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing polymer gas separation membrane has difficulty in taking into account both selectivity and permeability, which leads to poor performance in gas separation.

Method used

采用基于ZIF-8@MXene的混合基质膜,通过原位合成ZIF-8@MXene纳米片并将其填充到聚醚共聚酰胺(Pebax 1657)溶液中,制备出具有优异渗透性能和气体分离性能的膜。

Benefits of technology

The selectivity and permeability of gas separation are significantly improved, the selectivity of CO2/CH4 can reach 29.3, and the stability and mechanical properties of the membrane have also been improved, which can show good performance in industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455696A_ABST
    Figure CN119455696A_ABST
Patent Text Reader

Abstract

The invention provides a mixed matrix membrane based on ZIF-8 (at) MXene and a preparation method and application thereof, and belongs to the technical field of gas separation membranes. Through a two-dimensional material MXene, the diffusion path of gas in the membrane is lengthened and becomes more zigzag, the molecular sieving capacity of the membrane is enhanced, and the selectivity of gas separation is improved; the ZIF-8 crystals uniformly grown on the MXene in situ have high specific surface area, large pore volume and excellent thermal stability and chemical stability, the permeability of the membrane is effectively improved, and in the gas separation process, the ZIF-8 provides more transmission channels for CO2 molecules by virtue of the large pore volume and high specific surface area, so that the adsorption capacity of CO2 gas can be greatly improved, and the CO2 gas separation efficiency is improved. The CH4 diffusion is prevented by utilizing the low adsorption capacity of the adsorbent on CH4 molecules, so that an excellent gas separation effect is realized; and when the mixed matrix membrane passes through MXene, the selectivity of the gas to CH4 is obviously enhanced due to extension and complexity of a diffusion channel, and finally, the effect of simultaneously improving the selectivity and permeability of the mixed matrix membrane is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas separation membranes, and in particular to a mixed matrix membrane based on ZIF-8@MXene and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid development of industry and the sharp increase in population, the issue of global warming has received increasing attention, and the effective removal of CO2 has become particularly important. Common gases containing CO2 include synthesis gas tail gas (H2 / CO2), natural gas (CH4 / CO2), flue gas (N2 / CO2), etc. Separating and capturing CO2 from these gases can not only reduce the CO2 concentration in the gas and mitigate the greenhouse effect, but also greatly help to improve its commercial value and avoid the corrosion of acidic gases in pipeline transportation. Among them, the efficient capture of CO2 in natural gas (mainly CH4) is a key problem that needs to be solved urgently. In order to remove impurity gases (CO2) from natural gas, it is very important to develop a simple and efficient separation method. At present, the commonly used separation methods include solvent absorption, pressure swing adsorption, low-temperature separation and membrane separation. Although the first three traditional separation technologies are mature and have excellent separation performance, they also face problems such as high equipment investment, complex operation, high energy consumption and potential environmental pollution. In contrast, membrane separation technology has received widespread attention due to its advantages such as simple operation, low energy consumption and no pollution emissions. Therefore, membrane separation technology is considered to be an important way to achieve green and environmental protection in the field of CO2 separation in the future.

[0003] The research on the use of polymer membranes for gas separation started early, and its advantages such as low preparation cost and mature preparation process have led to its large-scale application in industry. However, the performance of the polymer material itself is limited by the Robeson upper limit, and it is difficult to have excellent permeability and gas separation performance at the same time. Inorganic membrane materials have regular pores, adjustable pore size and affinity, and can achieve separation by size screening and surface diffusion mechanism, which can overcome the trade-off effect. However, the preparation cost of inorganic membranes is high, defects are prone to occur during the preparation process, and it is difficult to prepare on a large scale, which in turn limits its application in gas separation. Therefore, providing a polymer gas separation membrane that has both excellent permeability and gas separation performance is a technical problem that needs to be solved urgently in the prior art. Summary of the invention

[0004] The purpose of the present invention is to provide a mixed matrix membrane based on ZIF-8@MXene and a preparation method and application thereof. The mixed matrix membrane based on ZIF-8@MXene prepared by the method provided by the present invention has excellent permeability and gas separation performance.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a mixed matrix membrane based on ZIF-8@MXene, comprising the following steps:

[0007] (1) Using a solvent and Pebax 1657 as raw materials, preparing a Pebax 1657 solution;

[0008] (2) mixing the Pebax 1657 solution obtained in step (1) with the ZIF-8@MXene composite material, and performing a first ultrasonic treatment to obtain a casting solution containing the ZIF-8@MXene filler;

[0009] The ZIF-8@MXene composite material is a ZIF-8@MXene nanosheet synthesized in situ;

[0010] (3) The casting solution containing ZIF-8@MXene filler obtained in step (2) is subjected to degassing, casting, vacuum drying and solvent evaporation in sequence to obtain a mixed matrix membrane based on ZIF-8@MXene.

[0011] Preferably, the concentration of Pebax 1657 in the Pebax 1657 solution in step (1) is 2 to 10 wt.%.

[0012] Preferably, the method for preparing the ZIF-8@MXene composite material in step (2) comprises the following steps:

[0013] S1. Mixing MAX powder with etching solution, stirring and etching to obtain multilayer MXene powder;

[0014] S2. The multilayer MXene powder obtained in step S1 is mixed with dimethyl sulfoxide and stirred to obtain DMSO-intercalated MXene;

[0015] After mixing the DMSO-intercalated MXene and deionized water, performing a second ultrasonication and centrifugation in sequence to obtain a MXene dispersion;

[0016] S3. The MXene dispersion obtained in step S2 is mixed with zinc nitrate hexahydrate solution and 2-methylimidazole solution, and then self-assembled to obtain a ZIF-8@MXene composite material.

[0017] Preferably, the MXene in step S1 is Ti3C2T x 、Ti2CT x 、Nb3C2T x 、V2CT x 、Mo2CT x At least one of the following, wherein T represents a surface functional group, and x represents the number of atoms.

[0018] Preferably, the mass ratio of the monolayer MXene powder in the MXene dispersion in step S3, the 2-methylimidazole in the 2-methylimidazole solution, and the Zn(NO3)2·6H2O in the zinc nitrate hexahydrate solution is 1:(0.8-3.5):(0.10-0.70).

[0019] Preferably, the temperature of the first ultrasound in step (2) is ≥70°C, and the time of the first ultrasound is 30 to 60 minutes.

[0020] Preferably, step (3) is performed in an environment with an air humidity of 5% to 20%.

[0021] The present invention also provides a mixed matrix membrane based on ZIF-8@MXene prepared by the preparation method described in the above technical solution, wherein the thickness of the mixed matrix membrane based on ZIF-8@MXene is 30 to 120 μm.

[0022] Preferably, the mass fraction of ZIF-8@MXene in the mixed matrix membrane based on ZIF-8@MXene to Pebax 1657 is 0.3-8wt%

[0023] The present invention also provides the application of the mixed matrix membrane based on ZIF-8@MXene described in the above technical solution in gas separation.

[0024] The present invention provides a method for preparing a mixed matrix membrane based on ZIF-8@MXene, wherein in-situ synthesized ZIF-8@MXene nanosheets (i.e., ZIF-8@MXene composite materials) are used as nanofillers and filled into a polyether copolyamide (Pebax 1657) solution to prepare a casting solution, and a film is formed by a solution evaporation method to obtain a mixed matrix membrane based on ZIF-8@MXene. The present invention utilizes the special structure of the two-dimensional material MXene to lengthen the diffusion path of the gas in the membrane and make it more tortuous, thereby enhancing the molecular sieving ability of the membrane and significantly improving the selectivity of gas separation; at the same time, the ZIF-8 crystals uniformly grown in situ on the MXene have a high specific surface area, a large pore volume, and excellent thermal stability and chemical stability, which effectively improve the permeability of the membrane. In the gas separation process, ZIF-8, with its large pore volume and high specific surface area, provides more transmission channels for CO2 molecules, which can greatly increase the adsorption of CO2 gas, and utilizes its low adsorption capacity for CH4 molecules to prevent CH4 diffusion, thereby achieving excellent gas separation effects, and the CO2 / CH4 selectivity can reach 29.3; and when passing through MXene, the selectivity of the gas for CH4 is significantly enhanced due to the extension and complication of the diffusion channel, ultimately achieving the effect of simultaneously improving the selectivity and permeability of the mixed matrix membrane, effectively solving the problem that the existing polymer gas separation membranes are difficult to balance selectivity and permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The selectivity-permeability performance diagram of the mixed matrix membranes based on ZIF-8@MXene prepared in Examples 1 to 5 of the present invention and the pure Pebax 1657 membrane prepared in Comparative Example 1;

[0026] Figure 2 This is a graph showing the relationship between the gas permeability coefficient and pressure of the mixed matrix membrane based on ZIF-8@MXene prepared in Example 1 of the present invention;

[0027] Figure 3 A comparison chart of the mixed matrix membranes based on ZIF-8@MXene prepared in Examples 1 to 5 of the present invention and the pure Pebax 1657 membrane prepared in Comparative Example 1 with the Robeson upper limit;

[0028] Figure 4 The SEM cross-sectional images are of the mixed matrix membranes based on ZIF-8@MXene prepared in Examples 1 to 5 of the present invention and the pure Pebax 1657 membrane prepared in Comparative Example 1, wherein: Figure 4 (a) is control example 1, Figure 4 (b) is Example 2, Figure 4 (c) is Example 3, (d) is Example 4, Figure 4 (e) is Example 1, Figure 4 (f) is Example 5;

[0029] Figure 5 This is a graph showing the change in gas permeability coefficient of the ZIF-8@MXene-based mixed matrix membrane prepared in Example 1 over time. DETAILED DESCRIPTION

[0030] The present invention provides a method for preparing a mixed matrix membrane based on ZIF-8@MXene, comprising the following steps:

[0031] (1) Using a solvent and Pebax 1657 as raw materials, preparing a Pebax 1657 solution;

[0032] (2) mixing the Pebax 1657 solution obtained in step (1) with the ZIF-8@MXene composite material, and performing a first ultrasonic treatment to obtain a casting solution containing the ZIF-8@MXene filler;

[0033] The ZIF-8@MXene composite material is a ZIF-8@MXene nanosheet synthesized in situ;

[0034] (3) The casting solution containing ZIF-8@MXene filler obtained in step (2) is subjected to degassing, casting, vacuum drying and solvent evaporation in sequence to obtain a mixed matrix membrane based on ZIF-8@MXene.

[0035] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.

[0036] The invention uses a solvent and Pebax 1657 as raw materials to prepare a Pebax 1657 solution.

[0037] In the present invention, the solvent is preferably a deionized water solution of anhydrous ethanol, n-butanol and acetic acid.

[0038] In the present invention, when the solvent is a deionized water solution of anhydrous ethanol, the method for preparing the Pebax 1657 solution is preferably: after mixing anhydrous ethanol and deionized water to obtain a deionized water solution of anhydrous ethanol, stirring and heating to 80-85° C., then adding Pebax 1657, and keeping stirring at 80-85° C. for 3-5 hours to obtain a Pebax 1657 solution.

[0039] In the present invention, the mass ratio of ethanol to water is preferably (5-10):(1-5) and more preferably (6-9):(2-4). The present invention controls the mass ratio of ethanol to water within the above range to optimize solution viscosity, membrane structure and separation performance, avoid too low concentration which may lead to membrane defects and insufficient mechanical properties, and avoid too high concentration which may lead to solution viscosity, increase membrane thickness, and affect permeation flux and selectivity.

[0040] In the present invention, the concentration of Pebax 1657 in the Pebax 1657 solution is 2-10 wt.%. The present invention controls the concentration of Pebax 1657 in the Pebax 1657 solution within the above range to provide a stable dissolution environment, optimize solution viscosity, enhance film quality, improve the microstructure and gas separation performance of the film, and reduce the environmental risks of the preparation process.

[0041] After obtaining the Pebax 1657 solution, the present invention mixes the Pebax 1657 solution and the ZIF-8@MXene composite material, performs a first ultrasound, and obtains a casting solution containing the ZIF-8@MXene filler.

[0042] In the present invention, the ZIF-8@MXene composite material is a ZIF-8@MXene nanosheet synthesized in situ.

[0043] In the present invention, the preparation method of the ZIF-8@MXene composite material preferably comprises the following steps:

[0044] S1. Mixing MAX powder with etching solution, stirring and etching to obtain multilayer MXene powder;

[0045] S2. The multilayer MXene powder obtained in step S1 is mixed with dimethyl sulfoxide and stirred to obtain DMSO-intercalated MXene;

[0046] After mixing the DMSO-intercalated MXene and deionized water, performing a second ultrasonication and centrifugation in sequence to obtain a MXene dispersion;

[0047] S3. The MXene dispersion obtained in step S2 is mixed with zinc nitrate hexahydrate solution and 2-methylimidazole solution, and then self-assembled to obtain a ZIF-8@MXene composite material.

[0048] In the present invention, the MAX powder is preferably mixed with an etching solution and then stirred and etched to obtain a multilayer MXene powder.

[0049] In the present invention, the chemical formula of the MAX is preferably Mn+1AXn (n is 1, 2 or 3), wherein M is preferably a transition metal element, more preferably at least one of Ti, Nb, V, and Mo; A is preferably an element of the III and IV main groups, more preferably at least one of Al, Si, and Ga; and X is preferably an element of C or N. In the present invention, the MAX is more preferably at least one of Ti3AlC2 and Ti2AlC.

[0050] In the present invention, the etching solution is preferably a solution containing HCl and lithium fluoride, more preferably a mixture of LiF and 9 mol / L HCl aqueous solution; the ratio of the mass of LiF to the volume of HCl aqueous solution is preferably 1.40-1.80 g: 15-20 mL. In the present invention, the stirring etching is preferably carried out at room temperature for 14-22 hours.

[0051] After the stirring and etching is completed, the present invention preferably sequentially performs deionization washing, centrifugation and vacuum drying on the product of the stirring and etching to obtain a multilayer MXene powder.

[0052] In the present invention, the deionized water washing is preferably performed until the pH of the washing solution is greater than 6. The present invention has no particular limitation on the centrifugal method, as long as solid-liquid separation is achieved. The present invention has no particular limitation on the vacuum drying method, as long as the residual solvent is removed.

[0053] In the present invention, the MXene is preferably Ti3C2T x 、Ti2CT x 、Nb3C2T x 、V2CT x 、Mo2CT x At least one of the following, wherein T represents a surface functional group, and x represents the number of atoms.

[0054] In the present invention, the T is preferably one of -F, =O, and -OH.

[0055] After obtaining the multilayer MXene powder, the present invention preferably mixes the multilayer MXene powder with dimethyl sulfoxide and performs stirring treatment to obtain DMSO-intercalated MXene.

[0056] In the present invention, the mass ratio of the multilayer MXene powder to dimethyl sulfoxide (DMSO) is preferably (10-30): 1. The present invention controls the mass ratio of the multilayer MXene powder to dimethyl sulfoxide (DMSO) within the above range to improve the exfoliation efficiency and dispersion stability of MXene and form a high-quality two-dimensional sheet structure.

[0057] In the present invention, the stirring treatment is preferably carried out at room temperature for 16 to 22 hours.

[0058] After the stirring treatment is completed, the present invention preferably centrifuges the product of the stirring treatment to obtain DMSO-intercalated MXene.

[0059] After obtaining the DMSO-intercalated MXene, the present invention mixes the DMSO-intercalated MXene with deionized water, and then sequentially performs a second ultrasound and centrifugation to obtain a MXene dispersion.

[0060] In the present invention, the second ultrasound time is preferably 0.5 to 3 hours; the second ultrasound power is preferably 70 to 100 W; and the second ultrasound temperature is preferably 20 to 30° C. The present invention controls the temperature, time and power of the second ultrasound within the above range to avoid damage to the MXene sheet caused by excessive temperature and excessive time, while ensuring sufficient power to improve the stripping efficiency, thereby obtaining a high-quality, stable two-dimensional structure.

[0061] The present invention has no particular limitation on the centrifugal method, and any technical solution known in the art may be used.

[0062] After obtaining the MXene dispersion, the present invention mixes the MXene dispersion with a zinc nitrate hexahydrate solution and a 2-methylimidazole solution, and then performs a self-assembly reaction to obtain a ZIF-8@MXene composite material.

[0063] In the present invention, the solvent of the 2-methylimidazole solution is preferably methanol; the ratio of the mass of 2-methylimidazole to the volume of methanol in the 2-methylimidazole solution is preferably (1-2.8) g: (50-100) mL. In the present invention, the solvent of the zinc nitrate hexahydrate solution is preferably methanol; the ratio of the mass of Zn(NO3)2·6H2O to the volume of methanol in the zinc nitrate hexahydrate solution is preferably (0.16-0.50) g: (50-80) mL.

[0064] In the present invention, the mass ratio of the MXene powder in the MXene dispersion, the 2-methylimidazole in the 2-methylimidazole solution, and the Zn(NO3)2·6H2O in the zinc nitrate hexahydrate solution is preferably 1:(0.8-3.5):(0.10-0.70), and more preferably 1:(1-2.8):(0.16-0.50). The present invention controls the mass ratio of the monolayer MXene powder, 2-methylimidazole, and Zn(NO3)2·6H2O within the above range to effectively regulate the crystal growth rate and morphology of ZIF-8, ensure uniform anchoring on the MXene sheet, and optimize the specific surface area, pore structure, and interface interaction of the composite material, thereby improving its gas separation performance.

[0065] In the present invention, the self-assembly reaction is preferably carried out at room temperature with stirring for 10 to 60 minutes. The present invention controls the temperature and time of the self-assembly reaction within the above range to adjust the growth rate and morphology of the ZIF-8 crystal, avoid structural defects caused by high temperature or too long reaction, and ensure uniform anchoring on the MXene layer, thereby improving the specific surface area, thermal stability and functional performance of the composite material.

[0066] After the self-assembly reaction is completed, the present invention preferably filters and vacuum-dries the product of the self-assembly reaction in sequence to obtain a ZIF-8@MXene composite material.

[0067] The present invention has no special limitation on the filtering method, and the solid-liquid separation can be achieved by using a technical solution well known in the art. The present invention has no special limitation on the vacuum drying method, and the residual solvent can be removed by using a technical solution well known in the art.

[0068] After obtaining the Pebax 1657 solution and the ZIF-8@MXene composite material, the present invention mixes the Pebax 1657 solution and the ZIF-8@MXene composite material, performs a first ultrasound, and obtains a casting solution containing a ZIF-8@MXene filler.

[0069] In the present invention, the temperature of the first ultrasound is preferably ≥70°C, the time of the first ultrasound is preferably 30 to 60 minutes, and the power of the first ultrasound is preferably 70 to 100 W. The present invention controls the temperature, time and power of the first ultrasound within the above range to promote the uniform dispersion of MXene@ZIF-8 in the Pebax matrix, avoid material structure damage caused by high temperature or too long time, and enhance the interface compatibility and gas separation performance of the mixed matrix membrane.

[0070] After obtaining the casting solution containing ZIF-8@MXene filler, the present invention sequentially degasses, casts, vacuum-dries and evaporates the solvent of the casting solution containing ZIF-8@MXene filler to obtain a mixed matrix membrane based on ZIF-8@MXene.

[0071] In the present invention, the degassing method is preferably static degassing, negative pressure degassing and ultrasonic degassing, and static degassing is more preferred. In the present invention, the static degassing is preferably standing at room temperature for 2 to 10 minutes. In the present invention, the negative pressure degassing is preferably at a pressure of -0.08 to 0.1 MPa for 15 to 60 minutes. In the present invention, the ultrasonic degassing is preferably ultrasonically treated at (70 to 100) W and (≥70°C)°C for 10 to 30 minutes. The present invention uses degassing to effectively remove bubbles generated during the mixing process, improve the uniformity of the material, enhance the structural density of the membrane, avoid the influence of bubble defects on the performance, improve the film forming quality of the membrane, reduce structural defects, thereby improving the density of the membrane and the gas separation performance and mechanical properties.

[0072] In the present invention, the casting is preferably performed in an environment with an air humidity of 5% to 20%.

[0073] In the present invention, the vacuum drying temperature is preferably 60-80°C in a constant temperature vacuum oven for 18-24 hours. The present invention uses vacuum drying to fully remove solvent residues, avoid membrane structural stress and defects caused by rapid or uneven drying, ensure the uniformity and stability of the membrane, and thus improve its gas separation performance and mechanical strength.

[0074] In the present invention, the method of evaporating the solvent is preferably to place the solvent in a vacuum oven and evacuate it for 18 to 24 hours. The present invention evaporates the solvent to accelerate the volatilization of the solvent, reduce the residual amount, avoid the damage of high temperature to the material properties, and prevent the formation of bubbles and stress in the membrane structure, thereby improving the uniformity and separation performance of the membrane.

[0075] The present invention also provides a mixed matrix membrane based on ZIF-8@MXene prepared by the preparation method described in the above technical solution.

[0076] In the present invention, the thickness of the ZIF-8@MXene-based mixed matrix membrane is 30 to 120 μm, more preferably 40 to 100 μm. In the present invention, the mass fraction of ZIF-8@MXene in the ZIF-8@MXene-based mixed matrix membrane to Pebax 1657 is preferably 0.3 to 8 wt%, more preferably 0.5 to 7 wt%.

[0077] The present invention also provides the application of the mixed matrix membrane based on ZIF-8@MXene described in the above technical solution in gas separation.

[0078] In the present invention, the gas separation is preferably CO2 / CH4 gas separation.

[0079] The preparation method provided by the present invention uses in-situ synthesized ZIF-8@MXene nanosheets as building units to construct a ZIF-8@MXene-based mixed matrix membrane with significantly enhanced permeability and selectivity, thereby solving the problem that it is difficult to balance selectivity and permeability in existing gas separation membranes.

[0080] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0081] The permeability coefficient and selectivity test process of the gas in the following examples and comparative examples are as follows:

[0082] The permeability performance of the mixed matrix membrane was tested under the operating conditions of 30-60°C and 0.4-1MPa, with the mixed gas components CO2 / CH4: 50 / 50 volume percent. Its permeability was obtained by the constant pressure-variable volume method. For the mixed gas test, the upstream mixed gas enters the top of the permeation cell through a pressure reducing valve, a filter and a rotary valve, and the pressure is adjusted by a back pressure controller. The gas permeates to the bottom through the mixed matrix membrane in the permeation cell, and helium is used as a purge gas to blow the permeated gas into the gas chromatograph to detect the concentration of each component, and the gas flux is measured with a soap bubble flowmeter. In all tests, a "stage-cut" (i.e., the ratio of permeate flow to feed flow) of less than 1% was maintained to avoid concentration polarization. Before the test, all other gases in the pipeline and membrane were evacuated with a vacuum pump.

[0083] Calculation of gas permeability coefficient and selectivity in mixed matrix membranes:

[0084]

[0085] Where A and B represent different gases. i is the permeability coefficient of gas i in the membrane, the unit is Barrer (1Barrer = 1×10 -10 cm 3 (STP)cm / (cm 2 sec cmHg)); L is the thickness of the film, cm; N i is the gas permeation flux, cm 3 / sec; A is the effective membrane area, cm 2 ;Δp i is the pressure difference across the membrane, cmHg; x i ,y i represent the molar concentrations of permeate gas and feed gas respectively.

[0086] Example 1

[0087] A method for preparing a mixed matrix membrane based on ZIF-8@MXene, comprising the following steps:

[0088] (1) 8.0 g of Pebax 1657 particles were accurately weighed and added to 92 g of ethanol / water (the mass ratio of the two was 70 / 30) solution, and refluxed and stirred at 80° C. for 3 h under nitrogen protection to dissolve, thereby preparing a Pebax solution with a mass concentration of 8 wt.%;

[0089] (2) taking 1 / 3 of the volume fraction of the Pebax1657 solution with a mass concentration of 8 wt.% obtained in step (1), adding 0.40 g of the ZIF-8@MXene composite material to the above polymer solution, stirring for 2 h until completely dissolved, and then mixing with the remaining Pebax 1657 solution, performing a first ultrasonic treatment for 15 min, and stirring for another 3 h to obtain a casting solution containing a uniformly dissolved ZIF-8@MXene filler;

[0090] The preparation method of the ZIF-8@MXene composite material in step (2) comprises the following steps:

[0091] S1. After mixing MAX powder Ti3AlC2 with an etching solution, stirring and etching was performed at room temperature for 18 hours, and the mixture was repeatedly washed with deionized water until the pH was > 6. The solid was collected by centrifugation and vacuum dried to obtain a multilayer MXene powder; the etching solution was composed of a mixture of LiF and a 9 mol / L HCl aqueous solution;

[0092] S2. The multilayer MXene powder obtained in step S1 is mixed with dimethyl sulfoxide and stirred for 18 hours to obtain DMSO-intercalated MXene;

[0093] After mixing the DMSO-intercalated MXene and deionized water, a second ultrasonic treatment for 2 h and centrifugation were performed in sequence to obtain a MXene dispersion;

[0094] S3. The MXene dispersion obtained in step S2 is mixed with zinc nitrate hexahydrate solution and 2-methylimidazole solution, and a self-assembly reaction is carried out at room temperature under stirring for 40 minutes, and the solid is collected by filtration and vacuum dried to obtain a ZIF-8@MXene composite material;

[0095] (3) The casting solution containing ZIF-8@MXene filler obtained in step (2) is allowed to stand for degassing, and then poured into a polytetrafluoroethylene culture dish, placed horizontally, and the air humidity is controlled to be 20%; then it is placed in a vacuum drying oven, vacuumed at room temperature of 20°C for 12 hours, and then the temperature is raised to 50°C for drying for 48 hours, and then the temperature is further raised to 80°C for drying for 48 hours, and the residual solvent is further removed. Finally, it is peeled off from the polytetrafluoroethylene culture dish to obtain a ZIF-8@MXene-based mixed matrix membrane with a ZIF-8@MXene loading of 5wt.% and a thickness of 40 to 100μm, referred to as 5wt.% ZIF-8@MXene / Pebax 1657.

[0096] Comparative Example 1

[0097] a) Accurately weigh 8.0 g of Pebax 1657 particles and add them to 92 g of ethanol / water (mass ratio is 70 / 30) solution, reflux and stir at 80°C for 3 h under nitrogen protection to dissolve, to obtain a Pebax 1657 solution with a mass concentration of 8 wt.%, and then let it stand. Ultrasonic degassing;

[0098] b) The Pebax 1657 solution obtained in step (1) is allowed to stand for degassing, and then poured into a polytetrafluoroethylene culture dish, placed horizontally, and the air humidity is controlled to be 20%; then it is placed in a vacuum drying oven, vacuumed at room temperature of 20°C for 12 hours, then the temperature is raised to 50°C and dried for 48 hours, and then the temperature is further raised to 80°C and dried for 48 hours, and the residual solvent is further removed. Finally, it is peeled off from the polytetrafluoroethylene culture dish to obtain a pure Pebax 1657 film with a thickness of 40 to 100 μm.

[0099] At 30°C and 0.4 MPa, the gas separation performance of the mixed matrix membrane based on ZIF-8@MXene prepared in Example 1 was tested, and the permeability coefficients of CO2 and CH4 were 319.8 Barrer and 10.9 Barrer, respectively. The selectivity of CO2 to CH4 was: Similarly, at 30°C and 0.4MPa, the pure Pebax 1657 membrane prepared in Comparative Example 1 was tested for gas separation performance, and the permeability coefficients of CO2 and CH4 were 167.8 Barrer and 8.7 Barrer, respectively. The selectivity of CO2 to CH4 is: By comparing the gas separation performance of the membranes prepared in Example 1 and Comparative Example 1, it can be found that after adding ZIF-8@MXene to the Pebax 1657 membrane, the separation and purification of CO2 and CH4 can be effectively achieved.

[0100] Embodiments 2 to 5

[0101] The preparation was carried out according to the method of Example 1, except that: the addition amounts of the ZIF-8@MXene composite material in step (2) described in Examples 2 to 5 were 0.04 g, 0.08 g, 0.25 g and 0.60 g, respectively, added to each of the above-mentioned polymer solutions, stirred for 2 h until completely dissolved, and then mixed with the respective remaining Pebax solutions, ultrasonicated for 15 min, and stirred for 3 h, to finally obtain ZIF-8@MXene-based mixed matrix membranes with ZIF-8@MXene loading amounts of 0.5 wt.%, 1 wt.%, 3 wt.% and 7 wt.%, respectively, which were abbreviated as 0.5 wt.% ZIF-8@MXene / Pebax 1657, 1 wt.% ZIF-8@MXene / Pebax 1657, 3 wt.% ZIF-8@MXene / Pebax 1657 and 7 wt.% ZIF-8@MXene / Pebax 1657, respectively.

[0102] The mixed matrix membranes prepared in Examples 1 to 5 and the pure Pebax 1657 membrane prepared in Comparative Example 1 were subjected to gas separation performance tests at 30°C and 0.4 MPa. The test results are shown in Table 1. The selectivity-permeability performance of the mixed matrix membranes based on ZIF-8@MXene prepared in Examples 1 to 5 of the present invention and the pure Pebax 1657 membrane prepared in Comparative Example 1 is shown in Table 1. Figure 1 shown.

[0103] Table 1 Gas separation performance statistics of mixed matrix membranes based on ZIF-8@MXene prepared in Examples 2 to 5

[0104]

[0105]

[0106] As can be seen from Table 1, with the increase of ZIF-8@MXene loading, the permeation flux of CO2 and CH4 shows an increasing trend, while the selectivity of CO2 / CH4 increases first and then decreases. When the loading is 5wt.%, the permeation selectivity is the maximum value, which shows that appropriately increasing the ZIF-8@MXene loading is beneficial to the separation performance of the membrane, but beyond this range, the increase in ZIF-8@MXene loading is not conducive to the membrane separation performance. In addition, the ZIF-8@MXene / Pebax 1657 mixed matrix membrane has a certain improvement in the selectivity of the gas separation system for CO2, which achieves the goal of simultaneously improving the permeability coefficient and selectivity, and its performance is close to the Robeson upper limit (such as Figure 3), indicating that the mixed matrix membrane has very ideal permeation separation performance when separating the above gas systems. The "Robeson upper bound" here is a graph formed by American scholar Robeson (Robeson LM, The upper bound revisited, Journal of Membrane Science, 2008, 320, 390-400) based on a large number of reported polymer membrane permeability data for specific gas molecules, with CO2 permeability coefficient as the horizontal axis and CO2 / CH4 selectivity as the vertical axis. The mixed matrix membrane based on ZIF-8@MXene prepared in Examples 1 to 5 of the present invention and the pure Pebax1657 membrane prepared in Comparative Example 1 are compared with the Robeson upper bound as shown in the figure below. Figure 3 As shown, Figure 3 Shown is the 2008 Robeson cap.

[0107] The effect of pressure (0.4-1 MPa) was studied on the ZIF-8@MXene mixed matrix membrane with a ZIF-8@MXene loading of 5 wt.% prepared in Example 1 (referred to as 5 wt.% ZIF-8@MXene / Pebax 1657). The relationship between the permeability coefficient and pressure is shown in Table 2. The relationship between the gas permeability coefficient and pressure of the ZIF-8@MXene mixed matrix membrane prepared in Example 1 is shown in Figure 2 shown.

[0108] Table 2 Statistics of the permeability coefficient of the mixed matrix membrane based on ZIF-8@MXene prepared in Example 1 as a function of pressure

[0109]

[0110]

[0111] From Table 2 and Figure 2 It can be seen that the permeability coefficient of CO2 of 5wt.% ZIF-8@MXene / Pebax 1657 mixed matrix membrane increases with the increase of pressure, but the permeability coefficient of CH4 does not change significantly. Therefore, in practical applications, appropriately increasing the operating pressure can improve the separation effect of this mixed matrix.

[0112] Embodiments 7 to 9

[0113] The mixed matrix membrane was prepared according to the method of Example 1, except that in step (1) of Examples 7 to 9, n-butanol, acetic acid and ethanol were used as solvents to prepare the Pebax solution.

[0114] The gas separation performance of the mixed matrix membranes prepared in Examples 7 to 9 was tested at 60° C. and 0.4 MPa. The test results are shown in Table 3.

[0115] Table 3 Statistics of gas separation performance of mixed matrix membranes prepared in Examples 7 to 9

[0116]

[0117] It can be found from Table 3 that when the solvent is ethanol and ethanol / water solution, the gas separation performance of CO2 of the corresponding mixed matrix membrane is better. When n-butanol and acetic acid are used as solvents, the gas separation performance of the corresponding mixed matrix membrane is not as good as ethanol and ethanol / water. Compared with ethanol / water as solvent, the selectivity of CO2 / CH4 of the corresponding mixed matrix membrane is slightly reduced when ethanol is used as solution. But in general, after adding ZIF-8@MXene, no matter what solvent is used, the gas separation performance of the prepared mixed matrix membrane is better than that of the pure polymer membrane.

[0118] Embodiment 10, 11

[0119] A mixed matrix membrane was prepared according to the method of Example 1, except that the degassing methods in step (3) of Examples 10 and 11 were respectively negative pressure degassing and ultrasonic degassing, the ultrasonic degassing was performed at 80W and ≥70°C for 20min, and the negative pressure degassing was performed at a pressure of -0.08MPa for 30min;

[0120] The mixed matrix membranes prepared in Examples 10 and 11 were tested for gas separation performance at 30° C. and 0.4 MPa. The test results are shown in Table 4.

[0121] Table 4 Gas separation performance of mixed matrix membranes prepared in Examples 10 and 11

[0122]

[0123] From the data in Table 4, it can be found that in the static degassing mode, the CO2 permeability coefficient and separation performance of the mixed matrix membrane prepared in Example 1 are the best, which are: The permeability coefficient and separation performance of the mixed matrix membrane prepared by negative pressure degassing and ultrasonic degassing are slightly lower than those of static degassing, indicating that static degassing is preferred among the three degassing methods when preparing the mixed matrix membrane.

[0124] Example 12

[0125] A mixed matrix membrane was prepared according to the method of Example 1, except that the amount of Pebax 1657 particles used in step (1) of Example 12 was 4 g, and a Pebax 1657 solution with a mass concentration of 4 wt.% was obtained.

[0126] Comparative Examples 2 and 3

[0127] A mixed matrix membrane was prepared according to the method of Example 1, except that the amounts of Pebax 1657 particles used in step (1) of Control Examples 2 and 3 were 1 g and 10 g, respectively, and Pebax 1657 solutions with mass concentrations of 1 wt.% and 10 wt.% were obtained, respectively.

[0128] The mixed matrix membrane based on ZIF-8@MXene prepared in Example 12 and the mixed matrix membranes prepared in Control Examples 2 and 3 were tested for gas separation performance at 30°C and 0.4 MPa. The test results are shown in Table 5.

[0129] Table 5 Gas separation performance of the mixed matrix membrane based on ZIF-8@MXene prepared in Example 12 and the mixed matrix membrane prepared in Comparative Examples 2 and 3

[0130]

[0131] From the data in Table 5, we can find that: when the mass fraction of Pebax 1657 in the solvent increases, the permeability coefficients of CO2 and CH4 decrease continuously; when the mass fraction is less than 8wt.%, the selectivity of CO2 / CH4 increases with the increase of mass fraction; but after the mass fraction exceeds 8wt.%, the permeability coefficient and selectivity decrease at the same time. Therefore, according to the above analysis, it is the best choice to control the mass fraction of Pebax1657 in the solvent to about 8wt.%.

[0132] The SEM cross-sectional images of the mixed matrix membranes based on ZIF-8@MXene prepared in Examples 1 to 5 of the present invention and the pure Pebax 1657 membrane prepared in Comparative Example 1 are shown in FIG. Figure 4 ,in, Figure 4 (a) is control example 1, Figure 4 (b) is Example 2, Figure 4 (c) is Example 3, (d) is Example 4, Figure 4 (e) is Example 1, and (f) is Example 5. Figure 4As shown in Figure 2, the cross-section of the pure Pebax1657 membrane exhibits a smooth, uniform and tightly packed microstructure. However, with the introduction of ZIF-8@MXene composites as nanofillers, obvious convex structures appeared on the cross-sectional surface of the prepared mixed matrix membrane, resulting in a significant increase in the roughness of the membrane compared with the pure membrane. When the filler loading was 0.5-5wt.%, ZIF-8@MXene was uniformly distributed in the Pebax matrix. This uniform dispersion was mainly attributed to the role of MXene nanosheets, which acted as an effective scaffold to promote the dispersion of ZIF-8 nanoparticles in the membrane matrix. However, when the ZIF-8@MXene nanofiller loading reached 7wt.%, the dispersion in the mixed matrix membrane gradually decreased, resulting in the formation of larger agglomerates, mainly due to the severe filler agglomeration in the corresponding mixed matrix membrane that destroyed the continuous polymer chain stacking. Therefore, strict control of the loading amount of ZIF-8@MXene nanofillers is crucial to ensure optimal dispersion and maintain the intended function of the membrane.

[0133] The stability of the membrane was investigated by running the CO2 / CH4 mixed gas in the 5wt.% ZIF-8@MXene / Pebax 1657 mixed matrix membrane for 120 hours continuously. The gas permeability coefficient of the mixed matrix membrane based on ZIF-8@MXene prepared in Example 1 was obtained as a function of time. Figure 5 As shown. Figure 5 It can be seen that the mixed matrix membrane based on ZIF-8@MXene prepared in Example 1 exhibited stable gas permeation performance during operation, and the permeation flux and selectivity did not change significantly, showing great potential in industrial applications. It is worth noting that the ZIF-8@MXene filler provides rigid support for the Pebax matrix, successfully preventing the collapse of the molecular chain. At the same time, ZIF-8@MXene increases the rigidity of the Pebax matrix, which helps to maintain the stability of the membrane. The results show that the 5wt.% ZIF-8@MXene / Pebax 1657 mixed matrix membrane can maintain good stability.

[0134] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a mixed matrix membrane based on ZIF-8@MXene, characterized in that: The following steps are involved: (1) Using a solvent and Pebax 1657 as raw materials, preparing a Pebax 1657 solution; (2) mixing the Pebax 1657 solution obtained in step (1) with the ZIF-8@MXene composite material, and performing a first ultrasonic treatment to obtain a casting solution containing the ZIF-8@MXene filler; The ZIF-8@MXene composite material is a ZIF-8@MXene nanosheet synthesized in situ; (3) The casting solution containing ZIF-8@MXene filler obtained in step (2) is sequentially subjected to degassing, casting, vacuum drying and solvent evaporation to obtain a mixed matrix membrane based on ZIF-8@MXene.

2. The preparation method according to claim 1, characterized in that: The concentration of Pebax 1657 in the Pebax 1657 solution in step (1) is 2 to 10 wt.%.

3. The preparation method according to claim 1, characterized in that: The method for preparing the ZIF-8@MXene composite material in step (2) comprises the following steps: S1. Mixing MAX powder with etching solution, stirring and etching to obtain multilayer MXene powder; S2. The multilayer MXene powder obtained in step S1 is mixed with dimethyl sulfoxide and stirred to obtain DMSO-intercalated MXene; After mixing the DMSO-intercalated MXene and deionized water, performing a second ultrasonication and centrifugation in sequence to obtain a MXene dispersion; S3. The MXene dispersion obtained in step S2 is mixed with zinc nitrate hexahydrate solution and 2-methylimidazole solution, and then a self-assembly reaction is performed to obtain a ZIF-8@MXene composite material.

4. The preparation method according to claim 3, characterized in that: The MXene in step S1 is Ti3C2T x 、Ti2CT x 、Nb3C2T x 、V2CT x 、Mo2CT x At least one of the following, wherein T represents a surface functional group, and x represents the number of atoms.

5. The preparation method according to claim 3, characterized in that: In the step S3, the mass ratio of the MXene powder in the MXene dispersion, the 2-methylimidazole in the 2-methylimidazole solution, and the Zn(NO3)2·6H2O in the zinc nitrate hexahydrate solution is 1:(0.8-3.5):(0.10-0.70).

6. The preparation method according to claim 1, characterized in that: The temperature of the first ultrasound in step (2) is ≥70°C, and the time of the first ultrasound is 30 to 60 minutes.

7. The method according to claim 1, characterized in that The casting in the step (3) is carried out in an environment with an air humidity of 5% to 20%.

8. The mixed matrix membrane based on ZIF-8@MXene prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The thickness of the ZIF-8@MXene-based mixed matrix membrane is 30 to 120 μm.

9. The preparation method according to claim 8, characterized in that: In the ZIF-8@MXene-based mixed matrix membrane, the mass fraction of ZIF-8@MXene in Pebax 1657 is 0.3-8 wt %.

10. Use of the mixed matrix membrane based on ZIF-8@MXene according to claim 9 in gas separation.